2007
DOI: 10.1161/atvbaha.107.144881
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Suppresses Prolyl-4-Hydroxylase α1 Expression via the ASK1–JNK–NonO Pathway

Abstract: Background-Inflammation is known to contribute to the pathogenesis of vascular diseases in which arterial wall extracellular matrix (ECM) homeostasis is disrupted. Tumor necrosis factor-␣ (TNF-␣), a pivotal cytokine that regulates ECM metabolism by increasing degradation and decreasing production of arterial collagens, is associated with vulnerable plaques and aortic aneurysms. Methods and Results-In the current study, we showed that, when administered in doses of 1 to 100 ng/mL, TNF-␣ dose-dependently downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 37 publications
(44 reference statements)
3
35
0
Order By: Relevance
“…28-30 Several studies have revealed that various cytokines, such as interleukins and TNF-α, inhibit the P4H isoenzymes. Zhang et al reported that TNF-α suppresses collagen synthesis by specifically inhibiting P4Hα1, 31 and Raveendran et al also showed that cigarette smoke extract can significantly downregulate the expression of P4Hα1. 32 However, little information exists on whether the defense molecules regulating the expression of P4Hα1 play a key role in plaque cap stability.…”
Section: Discussionmentioning
confidence: 99%
“…28-30 Several studies have revealed that various cytokines, such as interleukins and TNF-α, inhibit the P4H isoenzymes. Zhang et al reported that TNF-α suppresses collagen synthesis by specifically inhibiting P4Hα1, 31 and Raveendran et al also showed that cigarette smoke extract can significantly downregulate the expression of P4Hα1. 32 However, little information exists on whether the defense molecules regulating the expression of P4Hα1 play a key role in plaque cap stability.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation of the histones resulted in recruitment of the NonO protein, which has been shown to have a suppressive effect on gene transcription (Zhang et al, 2007). Through protein-protein interaction, nuclear actin, which binds on the 27nt repeat element, recruits HDAC3 to the site.…”
Section: Discussionmentioning
confidence: 99%
“…We further detected interaction between HDAC3 and NonO protein ( Figure 3B, middle left), and between nuclear actin and NonO ( Figure 3B, bottom left). Our previous work showed that NonO protein, when recruited to the target genomic location, is frequently associated with suppression of transcription (Zhang et al, 2007). The recruitment of the NonO protein to the HDAC3 and nuclear actin complex in the 27nt repeat region could be responsible for the suppressive effects of the 27nt small RNA on eNOS transcription.…”
Section: Protein-rna and Protein-protein Interactionmentioning
confidence: 99%
“…11 P4H expression is also regulated by NO, TNF-α, transforming growth factor-β, insulinlike growth factor-1, β fibroblast growth factor, cytokines, and even cigarette smoking as well. 12 It has been reported that the anti-atherogenic effect of adiponectin was in part mediated by its regulatory ability on collagen synthesis, 13 but precise molecular mechanism was unknown. In the current study by Li and co-workers, they newly identified that adiponectin is another player for the regulation of P4H expression.…”
Section: Article P 552mentioning
confidence: 99%